Prolonged antiretroviral therapy use and hypertension in a retrospective cross-sectional study-Rakai, Uganda - Grace Mongo Bua; Victor Ssempijja; Anthony Ndyanabo; Dorean Nabukalu; Jesca Basiima; Edward Nelson Kankaka; Fred Nalugoda; Gertrude Nakigozi; Joseph Kagaayi; Larry W. Chang; Wendy S. Post; Thomas C. Quinn; et al. (BMC Infectious Diseases)
Abstract Background While antiretroviral therapy (ART) reduces AIDS-related morbidity and mortality, it is unclear if prolonged ART use among people living with HIV (PLHIV) increases the risk of hypertension. Objective We assessed the association between the duration of ART use and hypertension in the Rakai Community Cohort Study (RCCS). Design We conducted a cross-sectional study among PLHIV (35–49 years old) on ART in the RCCS who were surveyed between August 2016 and May 2018. Methods Systolic and diastolic blood pressure (BP) was measured twice, averaged, and classified as any hypertension (systolic BP ≥ 140 mmHg or diastolic BP ≥ 90 mmHg), severe or worse hypertension (systolic BP ≥ 160 mmHg or diastolic BP ≥ 100 mmHg), or hypertensive crisis (systolic BP ≥ 180 mmHg or diastolic BP ≥ 110 mmHg). ART duration was categorized as short (0–2 years), moderate (> 2–5 years), or prolonged (> 5 years). We used log-binomial regression to estimate the adjusted prevalence ratio (adjPR) of hypertension associated with ART duration. Results A total of 1,144 PLHIV on ART with documented BP information were identified in the RCCS, of whom 173 (15.1%) had any hypertension, 64 (5.6%) had at least severe hypertension, and 44 (3.8%) had hypertensive crisis. After controlling for age, sex, and body mass index, the prevalence of having all stages of high BP was increased by at least 42% in participants with more than five years of ART use (any hypertension adjPRs = 1.42 [95% CI = 0.99–2.03]; severe hypertension adjPRs = 1.79 [95% CI = 1.01–3.15]; and hypertensive crisis adjPRs = 2.56 [95% CI = 1.14–5.77]). Conclusions PLHIV on long-term ART have a higher burden of hypertension, highlighting the need for enhanced screening and integrated management in HIV programs.